2005
DOI: 10.1007/s10900-004-1959-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Literacy Level of Patient Education Pages in Health-Related Journals

Abstract: The purpose of this study was to evaluate the reading level of patient education material from selected current health care journals. Ten patient education pages from a variety of health care journals were entered into a Microsoft Word program. Applying the Flesch-Kincaid readability formula available from Microsoft Word, a reading level for each page was established and compared to recommended standards. Only 2 of 10 patient education pages fell within the recommended reading levels for health-related materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
188
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(200 citation statements)
references
References 8 publications
9
188
1
2
Order By: Relevance
“…For this reason clinicians should identify patients who may struggle, using validated screening tools (Appendix 2) [18,75,78,103]. Despite this clinicians may fail to identify patients with low health literacy and should consider producing ''health-literate'' PROMs written at or below the level of an 11-year-old subject [21,40,106].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason clinicians should identify patients who may struggle, using validated screening tools (Appendix 2) [18,75,78,103]. Despite this clinicians may fail to identify patients with low health literacy and should consider producing ''health-literate'' PROMs written at or below the level of an 11-year-old subject [21,40,106].…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare organizations such as the National Work Group on Cancer and Health [13], American Medical Association [51], and National Institutes of Health [43] recommend the readability of patient information material should be no higher than sixth-grade level, while the Centers for Disease Control and Prevention (CDC) recommends the readability to be lower than eighth-grade level [11]. Given the variability in the capacity to comprehend health-related materials among individuals seeking orthopaedic care, stratifying the contents of patient education materials at different levels of complexity will be required to improve health literacy and enhance patient-centered communication.…”
Section: Where Are We Now? the Provider And Patient Educational Toolsmentioning
confidence: 99%
“…Several health organizations have made recommendations on various ways to improve the delivery of health-related information to the general population. It is important to substitute complex medical terms with simpler terms that can be found at Web sites such as http:// plainlanguage.gov/howto/wordsuggestions/index.cfm [13]. The ''Living Word Vocabulary'' [14] contains about 43,000 words arranged in various grade levels of complexity and can also be used to substitute difficult words [31].…”
Section: How Do We Get There? Improving Patient Education Materialsmentioning
confidence: 99%
“…Patients with inadequate functional health literacy have worse comprehension of physician instructions and tend to ask fewer questions in the medical encounter (Sudore et al, 2009). Many studies have shown that the medical information currently available and routinely given to patients is often at advanced reading levels (Cotugna, Vickery, & Carpenter-Haefele, 2005;Kirksey, Harper, Thompson, & Pringle, 2004). Given the importance of patient self-management of health and illness and the expectation to participate in decision making, patients are constantly forced to make complex decisions on multiple levels.…”
Section: B Gaglio Et Almentioning
confidence: 99%